2012
DOI: 10.1108/14691931211196213
|View full text |Cite
|
Sign up to set email alerts
|

IC disclosures in IPO prospectuses: evidence from Malaysia

Abstract: PurposeThis study aims to investigate the factors influencing the disclosure of intellectual capital (IC) information in the Malaysian initial public offering (IPO) prospectus using multiple regression analysis.Design/methodology/approachThe sample consists of 130 companies in the technology and industrial products sectors of Bursa Malaysia that went through an IPO between 2004 and 2008. Initially, the extent of the IC disclosure index is quantified using content analysis methodology. The multiple regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…In prior researches, results concerning the impact of the firm"s age on voluntary ICD are inconsistent. Researches like Li et al (2008), Rimmel et al (2009) and Rashid et al (2012) found a negative association. In the research of White et al (2007), was found a positive relationship.…”
Section: Profitabilitymentioning
confidence: 99%
“…In prior researches, results concerning the impact of the firm"s age on voluntary ICD are inconsistent. Researches like Li et al (2008), Rimmel et al (2009) and Rashid et al (2012) found a negative association. In the research of White et al (2007), was found a positive relationship.…”
Section: Profitabilitymentioning
confidence: 99%
“…Leverage does not significantly affect ICD as a whole. The result is in line with Ferreira et al (2012), Ousama et al (2012) , andMuttakin et al (2015) but is conflicting with Rashid et al (2012), Oliveira et al (2013), and Kamardin et al (2017) who find that leverage has insignificant effect of ICD. The insignificant effect of leverage on ICD may be caused by the lack of demand from creditors to disclose firm's non-financial information, especially regarding ICD; since for debitors, firm's capability to service its debts is the most important.…”
Section: Multiple Regression Analysismentioning
confidence: 51%
“…Meanwhile, Atan & Rahim (2012) do not find any significant relationship between profitability and ICD. Likewise, different results are present between the studies by Rashid et al (2012), Oliveira et al (2013), Haji & Ghazali (2013), and Whiting & Woodcock's research which finds that leverage is not significantly related with ICD. Other than using size, market share, profitability, and leverage as variables, this study also tries to measure the role of information asymmetry in IC disclosure, as done by Bruggen et al (2009) and Orens et al (2009).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Based on the phenomenon of practice and literature review of previous research it is known that IC is a very important resource for value creation and competitive advantage for the company in mod-ern business especially in the era of digital banking as it is today. Nevertheless, accounting standards (both in Indonesia and internationally) have not been able to provide guidelines for accurately recognizing and measuring IC, resulting in IC not being included in financial statements (Rashid et al, 2012;Widarjo & Bandi, 2018).…”
Section: Introductionmentioning
confidence: 99%